The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3139/113.110315
|View full text |Cite
|
Sign up to set email alerts
|

Cloud Point Extraction of Polycyclic Aromatic Hydrocarbons in Aqueous Solution with Nonionic Surfactants

Abstract: A cloud point extraction (CPE) process using the two nonionic surfactants, Tergitol 15-S-9 and Tergitol 15-S-7, mixtures of secondary ethoxylated alcohols, to extract selected polycyclic aromatic hydrocarbons (PAHs) from aqueous solutions at 25°C was investigated. Cloud point temperatures (CPTs) of selected nonionic surfactants were studied against the effect of added electrolytes on their cloud points. Sodium iodide could increase the cloud points of selected nonionic surfactants, i.e., the salt-in effect, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Up to now, non-ionic surfactants (mainly polyoxyethylenenated alkyl phenols, from PONPE 7.5 and Triton series such as Triton X-100 and Triton X-114) are the most widely employed for organic compounds analysis with CPE. [ 9 , 10 ]. Triton X-114 is well known for micelle formation compared to other classes of non-ionic surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, non-ionic surfactants (mainly polyoxyethylenenated alkyl phenols, from PONPE 7.5 and Triton series such as Triton X-100 and Triton X-114) are the most widely employed for organic compounds analysis with CPE. [ 9 , 10 ]. Triton X-114 is well known for micelle formation compared to other classes of non-ionic surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…As indicated by Katsoyannos et al [18], micellar systems using non-toxic surfactants (non-ionic, without branched aliphatic chains or aromatic moieties) are suitable for the isolation of natural antioxidants, which can then be used in dietary applications. Among non-ionic surfactants, polyethoxylates are the most numerous and technically interesting [15], standing out for their widespread use Triton (X-100 and X-114), Brij (−30, −56 and −97), Genapol (X-080), and to a lesser extent, the Tergitols (15-S-X), among others [19][20][21][22][23]. Genapol X-080 is a structured non-ionic surfactant of the ethoxylated primary aliphatic alcohols type, with a hydrophobic chain of 12 alkyls and 8 oxyethylene groups (OEs) in its hydrophilic region.…”
Section: Introductionmentioning
confidence: 99%
“…A major advantage of using micelles is that their transparency in the 240-280 nm region allows the monitoring of aromatic or conjugated systems more easily. In addition, nonionic surfactants have the capacity for developing interactions with wither hydrophobic or hydrophilic parts of the different molecules, allowing their extraction and purification more effectively [98,[275][276][277][278]. Specifically, upon extraction of PEITC (from watercress) with either alcohol ethoxylate non-ionic surfactants (e.g., Genapol X-080 and Tergitol 15-S-7) or a range of organic solvents of decreasing polarity (e.g., n-hexanes and a mixture of acetonitrile/chloroform; 10:7), results suggested that its extraction with non-ionic surfactants was the most efficient one.…”
Section: Extraction Of Phenethyl Isothiocyanatementioning
confidence: 99%